1)-3x+1+(x-5)=5(3-x)+5 2) -x+4+(x-5)=-2(-2-x)+5 3)2x+2+3(x+4)=-4(1-x)+3 Пожалуйста

1)-3x+1+(x-5)=5(3-x)+5 2) -x+4+(x-5)=-2(-2-x)+5 3)2x+2+3(x+4)=-4(1-x)+3 Пожалуйста
Гость
Ответ(ы) на вопрос:
Гость
1. -3x+1+(x-5)=5(3-x)+5 -3x+1+x-5=15-5x+5. -3x+x+5x=15+5-1+5. 3x=24. x=24:3. x=8 Ответ: x=8 2.  -x+4+(x-5)=-2(-2-x)+5  -х+4+х-5=4+2х+52x=-10   x=-5 Ответ: x=-5 3. 2x+2+3(x+4)=-4(1-x)+3 2x+2+3x+12=-4+4x+3 x=-15 Ответ: x=-15
Гость
1) -3x+1+(x-5)=5(3-x)+5 -3x+1+x-5=15-5x+5 -3x+x+5x=15+5-1+5 3x=24 x=24/3 x=8 2) -x+4+(x-5)=-2(-2-x)+5 -x+4+x-5=4+2x+5 -x+x-2x=4+5-4+5 -2x=10 x=10/-2 x=-5 3)2x+2+3(x+4)=-4(1-x)+3 2x+2+3x+12=-4+4x+3 2x+3x-4x=-4+3-2-12 x=-15
Не нашли ответ?
Ответить на вопрос
Похожие вопросы